Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1021/bi9827969
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Inhibition of Transcription Factor Binding to DNA by a Metallointercalator

Abstract: The metallointercalator Lambda-1-Rh(MGP)2phi5+ binds tightly and specifically to the site 5'-CATATG-3' in the major groove of double helical DNA by a combination of direct readout and shape selection. To examine competitive interactions between this small metal complex and a DNA-binding transcription factor, the preferred binding site for Lambda-1-Rh(MGP)2phi5+ was engineered into the AP-1 recognition element (ARE) of the major-groove binding bZIP transcription factor yAP-1, the yeast analogue of mammalian AP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…In agreement with this rationale, it has previously been demonstrated that MnTE-2-PyP oxidizes the p50 [40] and p65 subunits [18] of NF-ÎșB, which results in reduced DNA binding. Alternatively, other metalloporphyrins have been reported to bind directly to specific DNA sequences and potentially mask the transcription factor binding site [41]. Another manganese porphyrin, MnTM-4-PyP, has been shown to bind to RNA and DNA [42].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this rationale, it has previously been demonstrated that MnTE-2-PyP oxidizes the p50 [40] and p65 subunits [18] of NF-ÎșB, which results in reduced DNA binding. Alternatively, other metalloporphyrins have been reported to bind directly to specific DNA sequences and potentially mask the transcription factor binding site [41]. Another manganese porphyrin, MnTM-4-PyP, has been shown to bind to RNA and DNA [42].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, modification of a ruthenium complex with octaarginine allows for the facile uptake of complexes into the nuclei of cancer cells [34,35]. Functionalization of the ancillary ligands may also lead to sequence-selective recognition and cleavage by metallointercalators via hydrogen bonding or van der Waals interactions with modified ethylenediamine ligands [36–40], peptide sequences [41–43], or modified phen ligands [44–47], or nuclease activity [48]. …”
Section: Metal Complexes As Probes Of Dna Ctmentioning
confidence: 99%
“…Great concerns have been focused on developing metal complexes as diagnostic or therapeutic agents. The non-covalent binding of metal complexes with DNA has been used as synthetic restriction enzymes [11], DNA repair agents [12], selective probes of DNA structure [13], and artificial regulators of gene expression [14]. N 1 ,N 5 -bis[pyridine-2-methylene]-thiocarbohydrazone ligand and zinc (II) and nickel (II) schiff-base complexes were synthesized by Mishra and co-workers [15].…”
Section: Introductionmentioning
confidence: 99%